LIMBAH KAYU AKIBAT PEMBUATAN JALAN HUTAN DAN TEBANG BAYANG PADA ENAM HAK PENGUSAHAAN HUTAN DI KALIMANTAN TIMUR (Wood waste caused by forest road construction and shadow cutting at six logging companies in East Kalimantan) - Maman Mansyur Idris; Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1996)
This paper  present   the  results  of  the  study  on  logging  waste  caused  by forest   road construction and  shadow  cutting.  The  study  carried  out at  six  logging  companies  in East Kalimantan in 1990.The aim  of  the  study  are  :    (1)  to  determine  the  wood  waste  caused  by forest  road construction  and shadow cutting,  (2) to find the factors  influencing the wood waste and (3) to find the way of reducing the wood waste.The results  of this study  shows  that the average wood waste from trees felled caused by forest road construction  and shadow cutting is 1.16  m3/ha for  commercial wood species and 2. 76 m3/ha  for non-commercial  wood species.Keywords :  wood waste, forest road,  shadow cutting